Geomorphic function of large woody debris within a headwater tallgrass prairie stream network - Roberts, Brianna (Kansas State University, 2014)
Large woody debris, (LWD), defined as pieces measuring ≥ 1 meter in length and ≥ 10 centimeters in diameter (Swanson and Lienkaemper, 1978; Marston, 1982) is an influential stream component. Once stable LWD obstructs streamflow and regulates key processes, causing increases in storage capacity, scouring, and variations to the bed, the extent contingent upon LWD’s average length of residence time within a system. Several North American studies have acknowledged the effects of interactions between wood, sediment, and flow regimes (Bilby, 1981; Keller, E.A., and Swanson, F.J., 1979; Montgomery et al., 1995; Wohl, E., 2008), linking the triad to geomorphic changes, the redistribution of bed materials, and ecological benefits. A consensual baseline reference for LWD’s function over time does not exist however, partly due to previous research being primarily conducted in the Northeast and Pacific Northwest regions where historic actions of humans, particularly riparian logging and stream clearing, have greatly impacted the condition of the watersheds. Researchers having long-overlooked the Great Plains and other regions not commonly associated with woody vegetation has increased the ambiguity regarding the transferability of LWD findings between regions. By shifting the focus to a non-forested region, the goal of this thesis is to measure the dynamics and influence of a prairie stream’s wood load on sediment storage and bed morphology. The Kings Creek network study area is located on the Konza Prairie Biological Station in northeastern Kansas, and drains one of few remaining unaltered North American watersheds. Results document the ongoing forest expansion into the surrounding pristine grassland, and provide a temporal context of the regions changing climate representative of atypical stream conditions caused by drought. In total, 406 individual pieces of wood were measured. The wood load was lower than most forest streams referenced (13.05 m[superscript]³/100 m), though higher than expected resulting from the absence of streamflow. LWD stored 108 m[superscript]³ of sediment within the channel, and the cumulative volume of LWD-formed pools was 169 m[superscript]³. Additionally, statistical analysis showed longitudinal bed variations to be strongly associated to LWD abundance, further indicating that LWD influences prairie stream processes similarly to those in a forest stream.
Keywords: Fluvial geomorphology; Large woody debris; Sediment storage; Tallgrass prairie; Headwater streams; Riparian vegetation; Environmental Sciences (0768); Geomorphology (0484); Physical Geography (0368)